RELEVANSI NILAI DARI NILAI BUKU EKUITAS - Deni Darmawati (Media Riset Akuntansi, Auditing & Informasi, 2002)
The book value of equity can be used as a control variable to show relation-ship between share price and earning. Book value of equity becomes a variable that has a relevant value in economic perspective. There was not much a research to test the relevant value of book value of equity in Indonesia. The content of information of book value can be used to analyze shares price data besides earning.Keywords: Book value, Equity, Share price, Earning.